Effects of invisible orthodontic retainers on masticatory muscles activity during sleep: a controlled trial - Daniele Manfredini; Luca Lombardo; Letizia Vigiani; Angela Arreghini; Giuseppe Siciliani (Progress in Orthodontics, 2018)
Abstract Background This study aims to evaluate if invisible orthodontic retainers can affect sleep-time masticatory muscle activity (sMMA) over a short-term period in healthy individuals. Methods Nineteen (N = 19) healthy subjects underwent an in-home evaluation with a portable device for electromyographic (EMG) assessment. The study protocol provided two baseline recording nights, a night off, and then two additional nights with passive customized orthodontic retainers in situ. For each recording night, the sleep bruxism (SB) index (i.e., average number of SB events/hour) and the overall number of masseter muscle contractions were assessed. Comparison between values gathered over the four recording nights was made with a parametric test, based on the null hypothesis that there was no difference between wearing or not wearing the retainers as far as the sMMA variables are concerned. Results Average SB index of the first two nights without the retainers was 3.0 ± 1.5, whilst the average values with the retainers in situ was 3.6 ± 1.9. ANOVA test showed the absence of significant differences between the four nights. Similarly, no differences were shown between the four nights as for the total number of sMMA events. Based on that, the null hypothesis was not rejected. Conclusions Findings suggest the absence of relevant effects of invisible orthodontic retainers on sMMA in healthy individuals during the short-term period.